Translation and Technology: a Study of UK Freelance Translators - Heather Fulford; Joaquin Granell-Zafra (JoSTrans: The Journal of Specialised Translation)
There is a wide range of information and communications technologies (ICT) available to translators today, including both general-purpose software applications and special-purpose software, such as terminology management and translation memory systems. In this paper, the findings are reported of the first phase of a research project set up to investigate the adoption of information and communication technologies by UK freelance translators to support their various activities, including document production, terminology management, communication and client liaison, small business management, and marketing and work procurement. The findings reveal widespread adoption of general-purpose software applications, but only limited uptake of more special-purpose software, such as financial and accounting packages, terminology management tools and translation memory. Levels of awareness of translation-specific software were low, and many translators seemed sceptical about the value of such technologies. The implications of these findings are discussed for a number of stakeholders in the translation sector, including existing freelancers, newly-qualified translators, translator trainers, professional bodies for translators, and the developers and distributors of translation technologies.